Vaccination of Elk (Cervus canadensis) with Brucella abortus Strain RB51 Overexpressing Superoxide Dismutase and Glycosyltransferase Genes Does Not Induce Adequate Protection against Experimental Brucella abortus Challenge - Nol, Pauline; Olsen, Steven C.; Rhyan, Jack C.; Sriranganathan, Nammalwar; McCollum, Matthew P.; Hennager, Steven G.; Pavuk, Alana A.; Sprino, Phillip J.; Boyle, Stephen M.; Berrier, Randall J.; Salman, Mo D. (Frontiers in Cellular and Infection Microbiology, 2016)
In recent years, elk (Cervus canadensis) have been implicated as the source of Brucella abortus infection for numerous cattle herds in the Greater Yellowstone Area. In the face of environmental and ecological changes on the landscape, the range of infected elk is expanding. Consequently, the development of effective disease management strategies for wild elk herds is of utmost importance, not only for the prevention of reintroduction of brucellosis to cattle, but also for the overall health of the Greater Yellowstone Area elk populations. In two studies, we evaluated the efficacy of B. abortus strain RB51 over-expressing superoxide dismutase and glycosytransferase for protecting elk from infection and disease caused by B. abortus after experimental infection with a virulent B. abortus strain. Our data indicate that the recombinant vaccine does not protect elk against brucellosis. Further work is needed for development of an effective brucellosis vaccine for use in elk